2014
DOI: 10.1002/iub.1280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smad3 on the proliferation and steroidogenesis in human ovarian luteinized granulosa cells

Abstract: SummaryGranulosa cells (GCs) are essential for proper oocyte, follicular development, and steroidogenesis in the ovary. Transforming growth factor b (TGF-b) superfamily members are critical in regulating GCs growth and differentiation. Smad3 is known to serve as a signaling intermediate for the TGF-b; however, the functions of Smad3 in the human GCs remain unidentified. In this study, the luteinized GCs collected from follicular aspirates from patients undergoing in vitro fertilization were cultured and engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…11 In this study, we showed that TGF- β signaling enhanced FSHR expression and its intracellular signaling, consistent with previous reports in other mammals. 11, 12, 48 Addition of TGF- β increased FSHR mRNA expression in a time-dependent manner in rat GCs, 48 whereas TGF- β 1 in the presence of FSH decreased FSHR expression in bovine GCs. 14 SMAD3, a core component of TGF- β signaling, is a signaling intermediate for TGF- β .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…11 In this study, we showed that TGF- β signaling enhanced FSHR expression and its intracellular signaling, consistent with previous reports in other mammals. 11, 12, 48 Addition of TGF- β increased FSHR mRNA expression in a time-dependent manner in rat GCs, 48 whereas TGF- β 1 in the presence of FSH decreased FSHR expression in bovine GCs. 14 SMAD3, a core component of TGF- β signaling, is a signaling intermediate for TGF- β .…”
Section: Discussionsupporting
confidence: 92%
“…8 In this study, we further demonstrated that FSHR can control pGC apoptosis and follicular atresia. Moreover, silencing of FSHR decreased the levels of its intracellular signaling molecules such as PKA, 11 AKT, 30 and p-AKT in pGCs. In GCs, binding of FSH leads to the activation of FSHR, which can activate intracellular signaling.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations